2005
DOI: 10.1177/02711214050250040301
|View full text |Cite
|
Sign up to set email alerts
|

Early Head Start and Access to Early Intervention Services

Abstract: A Qualitative Investigation T his qualitative study of 32 low-income families with infants or toddlers with developmental delays or disabilities (a) examines whether participation in one Early Head Start (EHS) program increased the likelihood that the families would pursue early intervention services, (b) identifies the phases through which the EHS families progressed in accessing such services, and (c) describes how EHS helped the families obtain access. The study analyzes data from interviews, program record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…The risk factors were chosen based on factors that other studies have investigated or recommended for future studies with regards to follow-up adherence. The risk factors were the age 16 and gender 15,16,18,19,[33][34][35] of the child, maternal and caregiver age [15][16][17]19,21,23,35,36 , who the primary caregiver is, marital status of caregivers 19,20,37 , educational qualifications [15][16][17][18][19][20]23,35,36 , employment 18,20,35 , average household income [16][17][18][19][20]33,35,36 , type of housing 18 and number of people living in the household 35 . In addition, the effect of text message reminders on follow-up adherence was investigated 22,38 .…”
Section: Risk Assessment Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…The risk factors were chosen based on factors that other studies have investigated or recommended for future studies with regards to follow-up adherence. The risk factors were the age 16 and gender 15,16,18,19,[33][34][35] of the child, maternal and caregiver age [15][16][17]19,21,23,35,36 , who the primary caregiver is, marital status of caregivers 19,20,37 , educational qualifications [15][16][17][18][19][20]23,35,36 , employment 18,20,35 , average household income [16][17][18][19][20]33,35,36 , type of housing 18 and number of people living in the household 35 . In addition, the effect of text message reminders on follow-up adherence was investigated 22,38 .…”
Section: Risk Assessment Questionnairementioning
confidence: 99%
“…The positive effect of repeated reminders to follow-up on referrals has been demonstrated [22][23][24] . One study found that people who received text message reminders were 50% less likely to default on appointments 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Children from CLD backgrounds who live in low-income homes often face barriers that delay their development. These barriers include a lack of access to quality healthcare and social services, lack of exposure to experiences that promote early literacy, and the challenges of acquiring two languages concurrently (Iruka, 2009;Wall et al, 2005). Additionally, barriers faced by low income and CLD families often translate into significant stressors that overpower ethnic differences in family structural characteristics and parenting practices (Iruka, 2009).…”
Section: Considerations For Working With High Needs Familiesmentioning
confidence: 99%
“…Children with disabilities require early intervention programs for physical, developmental, and emotional rehabilitation (Wall et al., ). The IDEA necessitates that states have Early Childhood Intervention (ECI) programs that provide services to children with disabilities and their families.…”
Section: Available Resourcesmentioning
confidence: 99%
“…Due to the American with Disabilities Act and the Individual with Disabilities Education Act (IDEA), the number of children with disabilities living at home has doubled since 1960. In addition, these changes in governmental policy have affected the number of children with disabilities living at home and attending school (Reichman et al., ; Wall et al., ).…”
mentioning
confidence: 99%